A New Comparative Potentiometric Method for Analysis of Omarigliptin Using Three Different Sensors. Issue 1 (20th June 2022) - Kelani, Khadiga M.; Hegazy, Maha A.; Hassan, Amal M.; Tantawy, Mahmoud A.
Abstract: This work represents first attempt for potentiometric determination of the most recent antidiabetic; omarigliptin. Three sensors, employing potassium tetrakis (p‐chlorophenyl) borate as a lipophilic cation exchanger, were developed and compared. One liquid contact ion‐selective electrode and two carbon paste‐based solid contact ones, plain one and another one modified with polyaniline nanoparticles, were employed. Performances of fabricated sensors were assessed as per IUPAC recommendations. Incorporation of hydrophobic polyaniline nanoparticles as ion‐to‐electron transducer layer at solid contact/ion‐sensitive membrane interface enhanced sensitivity and stability of the third sensor showing LOD of 2.5×10 −7 mol L −1 and slope of 58.57 mV decade −1 . The three sensors were applied for omarigliptin determination in presence of its degradation products, in dosage form and spiked human plasma. Abstract :